Análise Economica da resposta do cajueiro anao precoce BRS 189 aos fatores de produçao agua e adubo potássico - Leite, Kelly Nascimento (2010)
For the success of the cashew culture as an agrarian enterprise, it is necessary to enhance farming techniques and crop management of cashew, ensuring efficient production and quality. The use of the production function allows the cashew grower to conceive optimal cultivation plans based on optimal levels of watering and fertilizing. Based on these considerations, this study was aimed at determining and analyzing the response of the dwarf cashew clone BRS 189 to the production factors water and potassium fertilizer, particularly from an economic viewpoint. The experiment was conducted in the D core of the Perímetro Irrigado (irrigated perimeter) Curu - Pentecoste (Ce), in the period from June to December 2009. The experimental design was randomized blocks with split plots consisting of four primary treatments in plots and four secondary treatments in subplots. Initial treatment consisted of 25, 50, 100 and 200% of the water volume lost by evapotranspiration by the culture, as estimated by a class A tank, and the secondary treatments consisted of applications of 0,50,100 and 200 g tree-1 year-1 of K2O. The cashew orchard was established in 2005 and this survey was done in the fourth year, a time when this culture reaches its full production potential. The clone used spaced 7.0m x 7.0m, irrigated by a micro-sprinkler irrigation system. Analysis consisted of two stages: post-harvest characteristics (TSS, average fruit weight, average length and diameter) and quantitative analysis (productivity). The results obtained led to the following conclusions: The potassium production factor had significant influence at the level of 8%, for the analyzed cashew post-harvest production variables. For the water production factor, however, only the variable average fruit weight showed significant influence, at the level of 5%. The maximum observed physical productivity, of 6665.7 kg ha-1, was obtained with treatment W3K2, referring to the watering equivalent to 100% of maximum crop evapotranspiration and an application of 100 g K2O-1 tree-1year-1 or 20.4 kg ha-1year-1. The estimated maximum yield (7600.9 kg ha-1) corresponded to an water requirement of more than 14.5% of the treatment W3 (100% ETm) and 140.5 g tree-1 year-1 of K2O, an amount equal to that recommended by soil analysis. The economically optimal watering level is 4.5% below the watering level observed to provide the highest productivity. Now, the economic productivity is only 1.4% lower than the productivity estimated by the statistical model, and saves 15.5% water, when compared with the watering requirements estimated by the physical model for maximum productivity.